(untitled) (Biodiversitas Journal of Biological Diversity, 2014)
Zarghi A, Hosseini SM. 2014. Effect of ecotourism on plant biodiversity in Chelmir zone of Tandoureh National Park, Khorasan Razavi Province, Iran. Biodiversitas 15: 224-228. Tourism in protected areas is generally viewed as a primary source of promoting economic and social growth to local communities and commonly perceived to safeguard biodiversity. However, in the last few decades an increasing number of visitors along with more diverse activities are having greater impacts on nature. Hence due to importance of ecotourism in Iran, the effect of ecotourism on plant biodiversity in Chelmir zone was investigated. To acquire the aim of the article, the sampling area was selected under the condition that the ecotourism is solely the variable factor and the slope, direction and height are considered constant factor after evaluation of the ecological land unit drawings. Two zones of high pressured and low pressured ecotourism were considered after evaluation of related drawings. Samples were taken in spring 2010. For evaluation of the plant biodiversity 60 samples of 1m2 (30 samples in each zone) were taken randomly and then the list of flora and the cover percentage of vegetation were recorded and then the percentage of vegetation data were analyzed in Biopast software and the biodiversity (Shanon, Simpson) richness (Menhinick, Margalef) evenness (Dominance, Berger-Parker) and dominance (Evenness, Equitability) indices were calculated. The mentioned indices were inserted in SPSS II software and the data normality was tested through Kolomogrov-Smirnov test. Due to data normality, non-paired T test was used in order to compare diversity analysis. The results indicate that the diversity, richness, dominance and evenness indices show significant effects of ecotourism on biodiversity indices.